2018
DOI: 10.5194/nhess-18-3203-2018
|View full text |Cite
|
Sign up to set email alerts
|

Roads and landslides in Nepal: how development affects environmental risk

Abstract: Abstract. The number of deaths from landslides in Nepal has been increasing dramatically due to a complex combination of earthquakes, climate change, and an explosion of informal road construction that destabilizes slopes during the rainy season. This trend will likely rise as development continues, especially as China's Belt and Road Initiative seeks to construct three major trunk roads through the Nepali Himalaya that adjacent communities will seek to tie in to with poorly constructed roads. To determine the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 13 publications
1
54
2
Order By: Relevance
“…However, benefits of roads need to be weighed alongside evidence that roads may benefit nonpoor households more, perhaps making development less even (Hettige, 2006). Furthermore, other impacts, such as increased environmental hazards, pollution, crime and unwanted cultural influences, are often overlooked (Blaikie et al, 1976;Hettige, 2006;Jaboyedoff et al, 2016;Murton, 2016). This paper builds on research and publications questioning the aspirations of the government of Nepal as early as the 1970s and 1980s.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, benefits of roads need to be weighed alongside evidence that roads may benefit nonpoor households more, perhaps making development less even (Hettige, 2006). Furthermore, other impacts, such as increased environmental hazards, pollution, crime and unwanted cultural influences, are often overlooked (Blaikie et al, 1976;Hettige, 2006;Jaboyedoff et al, 2016;Murton, 2016). This paper builds on research and publications questioning the aspirations of the government of Nepal as early as the 1970s and 1980s.…”
mentioning
confidence: 99%
“…Studies have demonstrated that roads are one of the 658 K. Sudmeier-Rieux et al: Invited perspectives: Mountain roads in Nepal at a new crossroads greatest anthropogenic drivers of environmental degradation, erosion and landslides in Nepal (Petley et al, 2007;Froude and Petley, 2018;Vuilliez et al, 2018). This situation is worsening due to the intensifying rainfall during the monsoon, largely attributed to climate change (Petley et al, 2007;Bharti et al, 2016;Devkota et al, 2018;Froude and Petley, 2018), which has led to a greater occurrence of landslides, especially in the middle hills (McAdoo et al, 2018). The possibility of an earthquake of even greater magnitude than the 2015 Gorkha earthquake (M 7.8) raises concerns about poorly designed roads increasing the likelihood of catastrophic landslides (Singh, 2018).…”
mentioning
confidence: 99%
“…Investment in roads is considered to bring multiple opportunities for enhancing livelihoods [2]. However, studies showed that, over the period of about 20 years, haphazard construction of rural roads increased exponentially in Nepal [3,4], and these roads are mostly unplanned and non-engineered [5], resulting in many slope failures that can create catastrophic disasters such as landslides. Unplanned human interventions, such as rural road construction, quarrying or poor terrace management can increase the fragility of slopes and, consequently, the occurrence of landslides and erosion [6].…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned human interventions, such as rural road construction, quarrying or poor terrace management can increase the fragility of slopes and, consequently, the occurrence of landslides and erosion [6]. Landslides not only destroy lives and livelihood activities, but they also block roads while causing long-term environmental degradation [3,7]. Nepal's hill roads are impacted by landslides mostly triggered by intense rainfall [8].…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines for landslide risk zoning and land use planning with the framework, definitions and recommendations were provided for different clearly defined scales (Fell et al, 2008a). Also, research work highlighting landslide risks at a community-level has recently been tested, and some of the result reached are open for the public (Abdulwahid and Pradhan, 2016;Chen et al, 2016a;Erener and Düzgün, 2012;Liu et al, 2016;McAdoo et al, 2018;Paliaga et al, 2019). Paliaga et al (2019), for example, have used a spatial multi-criteria analysis technique (SMCA) to mitigate geo-hydrological risk in a small but densely-populated catchment, with descriptive parameters of the extent of urban development and elements at risk.…”
Section: Introductionmentioning
confidence: 99%